Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4nj01431f
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible phosphate anchored Fe3O4 nanocarriers for drug delivery and hyperthermia

Abstract: Development of water-dispersible phosphate anchored Fe3O4 magnetic nanocarriers by conjugation of bioactive sodium hexametaphosphate for drug delivery and hyperthermia applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Magnetite (Fe 3 O 4 ) nanoparticles (NPs) have been developed for their fundamental scientific and technological interest including magnetic energy storage, 1 cell separation, 2 targeted drug delivery, 3 selective enrichment, 4 hyperthermia treatment, 5 and magnetic resonance imaging (MRI). 6 Control of the size and different morphologies (spherical, octahedral and cubic) of monodisperse Fe 3 O 4 NPs is very important because these various structures generate distinct properties.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetite (Fe 3 O 4 ) nanoparticles (NPs) have been developed for their fundamental scientific and technological interest including magnetic energy storage, 1 cell separation, 2 targeted drug delivery, 3 selective enrichment, 4 hyperthermia treatment, 5 and magnetic resonance imaging (MRI). 6 Control of the size and different morphologies (spherical, octahedral and cubic) of monodisperse Fe 3 O 4 NPs is very important because these various structures generate distinct properties.…”
Section: Introductionmentioning
confidence: 99%
“…18 Sahoo et al demonstrated the conjugation of alkyl phosphonates and phosphate to Fe 3 O 4 nanoparticles via formation of P-O-Fe bonding. 19 The formation of these water dispersible Fe 3 O 4 nanoparticles has been attributed to the presence of bioactive phosphate molecules on their surface. 19 The formation of these water dispersible Fe 3 O 4 nanoparticles has been attributed to the presence of bioactive phosphate molecules on their surface.…”
Section: Introductionmentioning
confidence: 99%
“…The NĂ©el and Brownian relaxation losses are associated with the magnetic moment rotations within the particles (due to internal fluctuations of the magnetic moment with respect to the crystal lattice) and with the entire particles (due to mechanical friction with the surrounding medium when nanoparticles keep oscillating toward the field, keeping its magnetic moment fixed along the crystal axis), respectively. The relaxation times are given by the following equations 31,32 : k is Boltzmann's constant, T is temperature, η is the viscosity and H R is the hydrodynamic particle radius. The use of magnetic nanoparticles in hyperthermia therapy depends on their heating efficiency, which is expressed in terms of the specific absorption rate (SAR).…”
Section: Resultsmentioning
confidence: 99%